2012
DOI: 10.1186/bcr3117
|View full text |Cite
|
Sign up to set email alerts
|

Premenopausal serum androgens and breast cancer risk: a nested case-control study

Abstract: IntroductionProspective epidemiologic studies have consistently shown that levels of circulating androgens in postmenopausal women are positively associated with breast cancer risk. However, data in premenopausal women are limited.MethodsA case-control study nested within the New York University Women's Health Study was conducted. A total of 356 cases (276 invasive and 80 in situ) and 683 individually-matched controls were included. Matching variables included age and date, phase, and day of menstrual cycle at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
42
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 57 publications
6
42
0
Order By: Relevance
“…Studies in both older premenopausal and postmenopausal women have shown that circulating androgens have good temporal reliability, i.e. one measurement ranks women reasonably well in terms of mid- to long-term average concentration [32, 33]. Though we are not aware of any study that examined how well circulating testosterone and free testosterone concentrations track before and after menopause in the same women, if ranking is preserved and women who have higher levels before menopause also have higher levels after menopause, the association we observed between premenopausal levels with risk of postmenopausal endometrial cancer could be due to the increased peripheral production of estrogens from increased androgen concentrations during the postmenopausal years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in both older premenopausal and postmenopausal women have shown that circulating androgens have good temporal reliability, i.e. one measurement ranks women reasonably well in terms of mid- to long-term average concentration [32, 33]. Though we are not aware of any study that examined how well circulating testosterone and free testosterone concentrations track before and after menopause in the same women, if ranking is preserved and women who have higher levels before menopause also have higher levels after menopause, the association we observed between premenopausal levels with risk of postmenopausal endometrial cancer could be due to the increased peripheral production of estrogens from increased androgen concentrations during the postmenopausal years.…”
Section: Discussionmentioning
confidence: 99%
“…A single blood sample was used to measure circulating androgens. We and others have shown, though, that among premenopausal women the reliability of measurements over a period of two years or more is high for testosterone, free testosterone, and DHEAS (intra-class correlations, ICCs, > 0.73) and moderate for androstenedione (ICCs > 0.57) [42, 33]. Inter-batch CVs were as high as 15–22% for some of the androgen measurements; however, intra-batch CVs were <12% and all samples from one matched set were always assayed in the same batch.…”
Section: Discussionmentioning
confidence: 99%
“…Although little is known about the role of androgens in age-related involution, testosterone may influence TDLU counts as a precursor in estrogen production (36, 37). Higher androgen levels have also been associated with breast cancer risk and risk factors (e.g., older age, natural menopause, higher BMI, and smoking) among both postmenopausal (19, 20, 35, 38, 39) and premenopausal women (21, 37, 40, 41). Null associations between SHBG and TDLU counts were consistent with past breast cancer risk studies among premenopausal women (21), but not postmenopausal women where inverse associations have been observed (20).…”
Section: Discussionmentioning
confidence: 99%
“…A further limitation of this and previous studies is that participants provided a single blood sample. The stability of hormone measurements over time has been shown previously for a period over at least 2 to 3 years, for both premenopausal 45,46 and postmenopausal women, 47 however, a single measurement may not accurately reflect a woman's average blood concentration over longer time periods. Circulating hormone concentrations may not adequately reflect concentrations at the tissue level and paracrine exposure may be of specific importance for ovarian cancer because the ovarian surface epithelium is not vascular.…”
Section: Discussionmentioning
confidence: 99%